Gender specific sexual dysfunction in patients with depression - Liu, Xinyu; Feng, Zizhao; Galling, Britta; Qi, Na; Zhu, Xue-quan; Xiao, Le; Wang, Gang (Frontiers in Psychiatry, 2023)
Background This study aims to investigate the factors associated with sexual dysfunction (SD), with a particular focus on the influence of sex on the occurrence and severity of this condition in patients with major depressive disorder (MDD). Method Sociodemographic and clinical assessments were conducted on 273 patients with MDD (female = 174, male = 99), including the ASEX, QIDS-SR16, GAD-7, and PHQ-15. Univariate analyses, independent samples t-test, Chi-square test, and Fisher’s exact test were used as appropriate, and logistic regression analysis was used to identify correlation factors for SD. Statistical analyses were performed using the Statistical Analysis System (SAS 9.4). Result SD was reported in 61.9% of the participants (ASEX score = 19.6 ± 5.5), and the prevalence of it in females (75.3%, ASEX score = 21.1 ± 5.4) was significantly higher than that in males (38.4%, ASEX score = 17.1 ± 4.6). Factors associated with SD included being female, being aged 45 years or above, having a low monthly income (≤750 USD), feeling more sluggish than usual (a QIDS-SR16 Item 15 score of 1 or above), and having somatic symptoms (evaluated with the total score of PHQ15). Limitation The use of antidepressants and antipsychotics might be a confounding factor affecting sexual function. Also, the lack of information in the clinical data regarding the number, duration, and time of onset of the episodes limits the richness of the results. Conclusion Our findings reveal the sex differences in the prevalence and severity of SD in patients with MDD. Evaluated with the ASEX score, female patients showed significantly worse sexual function than male patients. Being female, having a low monthly income, being aged 45 years or above, feeling sluggish, and having somatic symptoms may increase the risk of SD in patients with MDD.